Kemampuan Perhatian Anak Autisme Pada Permainan Puzzle Di SLB Melati Rumbai Pekanbaru - Norlita, Wiwik; Isnaniar; Sari, Maya (As-Shiha: Jurnal Kesehatan, 2021)
Autism or commonly called ASD Autistic Spectrum Disorder is a complex and highly varied disorder of development of brain function spectrum, usually these disorders include how to communicate, interact socially and imagine abilities. The concentration ability of autistic children is very low, this can be seen from the child's lack of ability to focus on when working on something, his attention is easily distracted, and often the child has difficulty in carrying out instructions. The purpose of this study is to find out the ability of attention of children with autism in puzzle games. This study used a descriptive method by retrieving using total sampling, with a total of 10 respondents. Based on the results of the study conducted on July 27 - August 7 2020 with the title of the study "Attention Ability of Children with Autism In Puzzle Games In SLB Melati Rumbai Pekanbaru" by observing ceklis sheet directly then can be concluded from 10 respondents, the results showed that the majority of respondents had a very well-categorized ability as many as 6 respondents (60.0%), both as many as 2 respondents (20.0%), less than 1 respondent (10.0%), and failed as many as 1 respondent (10.0%). The results of the study, according to the researchers, can be influenced by the level of ability of each respondent, from the researchers' observations, the age and gender of the respondent has no effect on the level of attention ability of the child with autism. Keywords : Autism, attention skills, Puzzle